Preparation and Bacteriostatic Properties of a Novel Hand Sanitizer Based on Graphene, Nanosilver, and Chitosan - Lei, Kang Li; Zhang, Ting (Recent Innovations in Chemical Engineering, 2025)
<span class=
Keywords: Escherichia coli